Lo sguardo territorialista di Leonardo Il cartografo, l'ingegnere idraulico, il progettista di città e territori - Poli, Daniela (Territori, 2023)
During the celebrations for Leonardo's fifth centenary, and under the patronage of their Italian Committee, a "21st century workshop of knowledge" worked eagerly in an interdisciplinary key, ranging on many aspects (from engineering to philosophy of nature, to history of architecture, reading of sources, technical knowledge, project analysis, cartographic interpretation), with the aim of contributing to the advancement of studies on an artist-researcher who synthesized the knowledge of his time in an extraordinary verbal-visual language, pushing them forward with anticipations and intuitions which are still relevant for the contemporary project, interpreting the territory as a common good and a living being. The volume presents the outcomes of this intense work.